Social networking using web services - Chakravaram, Vijay (Kansas State University, 2016)
Web services have expanded to become popular in application development. Web services technology represents an important way of communication between different applications across different platforms. Unlike traditional client/server models, such as a Web application or Web page system, Web services do not provide the user with a GUI. Instead, Web services share business logic, functionality and data through a programmatic interface across a network. Web services are services or functionalities that are exposed to the internet and serves as online or web APIs. These services which are online APIs can be called from your code and use the results in your applications to offer specific functionality to users. This project consists of two applications the client and the server application. The server application is an online REST API (Web Services developed using REpresentational State Transfer (REST) protocol) which provides all the functionalities as a service across the network that are required to develop a social networking web application. The client application is similar to any other social networking web application where you can create a profile, delete profile, send messages to your friends, post things, like and comment a post. This applications sends request to the server application using HTTP requests and get the responses. These responses are then consumed in the application to provide the required functionalities to the end user.
Keywords: Web Services; Hibernate; Java; JSP; Social Networking; RESTful API